A construção do violão mineiro: singularidades, estilos e identidades regionais na música popular instrumental de Belo Horizonte - Daniel Menezes Lovisi (2017)
The present essay aims to analyze the construction process of the so-called violão mineiro, a name proposed in the album Quadros Modernos, released in 2001 by three composers and guitar players from Minas Gerais: Chiquito Braga, Toninho Horta and Juarez Moreira. As part of the Brazilian popular music scenario of production, the work of these musicians whose careers started in the decades of 1960 and 1970 is important for its reinforcement of the position of a group of musicians from Belo Horizonte as representatives of what would become a typical guitar school started in Minas Gerais. By analyzing the dynamics of the scenario built by this group and its context, the objective of this work is to understand from the perspective of the creators which factors were determinant in propelling the production of instrumental guitar music in the capital of the state. The topics of interest of this research are, among others: a) the understanding of how instrumental music from Minas connected with the music created by representatives of the MPB movement in the state in the 1960s, absorbing and reinventing meanings created by the latter; b) the comprehension of how some composers and guitar players utilized aspects of a regional culture and identity through verbal and non-verbal expressions, connecting them to their work; c) to identify the principal aesthetical elements inside compositions and arrangements created by Chiquito Braga, Toninho Horta, Juarez Moreira e Gilvan de Oliveira and link them to the creation of a specific field of artistic production inside instrumental music field